Automatic composition of Learning Grid Portlets: a comparison of syntactic and semantic approaches. (19th August 2009) - Gutierrez-Carreon, Gustavo; Daradoumis, Thanasis; Jorba, Josep
Due to their potential advantages, the use of Grid technologies towards the development of collaborative and personalised learning frameworks has been considerably increased. These learning frameworks can be constructed based on distributed learning services and resources. A problem still unsolved is how to use and integrate low-level learning services to compose more complex high-level learning services or tools. In that sense, on the one hand, Business Process Execution Language (BPEL) is an orchestration language that, based on a syntactic representation of the characteristics of a learning service, can carry out the composition of a new learning service; on the other hand, Web Service Modeling Ontology (WSMO) is a language that can be used to represent the functional characteristics of a learning service semantically. This paper presents the benefits and limitations of the processes of composing learning portals based on Grid learning services using BPEL and WSMO.